2017
DOI: 10.1017/pan.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Guessing Components in the Measurement of Political Knowledge

Abstract: Due to the crucial role of political knowledge in democratic participation, the measurement of political knowledge has been a major concern in the discipline of political science. Common formats used for political knowledge questions include multiple-choice items and open-ended identification questions. The conventional wisdom holds that multiple-choice items induce guessing behavior, which leads to underestimated item-difficulty parameters and biased estimates of political knowledge. This article examines gue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…(2014), our five questions covered temporal (static and surveillance) and topical (policy‐specific and general) dimensions. To avoid problems with differential rates of “don't know” responses, we used a forced‐choice, five‐option multiple choice format, which can more accurately assess partially informed participants (Tsai & Lin, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2014), our five questions covered temporal (static and surveillance) and topical (policy‐specific and general) dimensions. To avoid problems with differential rates of “don't know” responses, we used a forced‐choice, five‐option multiple choice format, which can more accurately assess partially informed participants (Tsai & Lin, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…To avoid problems with differential rates of "don't know" responses, we used a forced-choice, fiveoption multiple choice format, which can more accurately assess partially informed participants (Tsai & Lin, 2017).…”
Section: Political Knowledgementioning
confidence: 99%
“…The literature has revealed that examinees frequently exclude some options from the possible answers based on their partial knowledge before guessing (e.g., Lindquist & Hoover, 2015). This behavior is referred to as educated guessing (Wu et al, 2021) or informed guessing (Tsai & Lin, 2017;Wu et al, 2019). Fitting the MC-DINA or MC-S-DINA models to the responses associated with partial knowledge would lead to the overestimation of attribute mastery states because the models that do not consider partial knowledge tend to under-evaluate the probability of correctly answering the items.…”
Section: Introductionmentioning
confidence: 99%
“… 3. Some research discusses guessing behavior and differentiates between blind guessing and informed guessing. Informed guessing is arguably more common than blind guessing when answering multiple-choice questions (Delli Carpini and Keeter, 1996; Mehrens and Lehmann, 1987; Mondak, 1999); it has been shown that partially informed respondents are more likely to guess the correct answers than uninformed or misinformed ones (Tsai and Lin, 2017). …”
mentioning
confidence: 99%